PERBANDINGAN BETON PASIR PANTAI DENGAN BAHAN TAMBAH SUPERPLASTICIZER TERHADAP KUAT TEKAN - Angga Hidayat; Marchellio Aprilian Prastama; Ignatius Sudarsono (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2026)
The scarcity of river sand has encouraged the utilization of sea sand as an alternative fine aggregate. However, its excessively fine gradation and salt content may potentially reduce concrete quality. This study aims to analyze the effect of sea sand with added superplasticizer on the compressive strength of concrete. Experiments were conducted to produce concrete using beach sand from two locations (Citepus and Batu Bintang) with superplasticizer concentrations of 1% and 2%. Cylindrical specimens were tested at the ages of 3, 7, 14, and 28 days. The test results showed that sea sand produced reasonably good compressive strength, and the addition of superplasticizer improved early-age strength. Concrete using beach sand from Batu Bintang combined with 2% superplasticizer achieved the best performance, with an average compressive strength of 24.5 MPa at 28 days, exceeding the design strength of f’c 20 MPa. This study concludes that beach sand can be used as fine aggregate with appropriate treatment and mix design, and superplasticizer is effective in enhancing workability. However, its Influence on compressive strength depends on the sand quality.